#healing as a form of expression among Malaysian TikTokers: fostering connections - Chairozila Mohd Shamsuddin,; Normazidah Che Musa,; Suziana Mat Saad,; Nur Elya Haifaa Mohamad Rizal, (Penerbit Universiti Kebangsaan Malaysia, 2023)
The current increasing interactions on social media have created complex patterns of meaning-making among TikTok users, such as the usage of hashtags as extensions of social meanings. In the social media app, TikTok, users are currently using the app to express their emotions, mostly through views and likes as an extension of their feelings. The usage of these hashtags is also open to different interpretations and misunderstandings among those unfamiliar with the conventions. This study aims to investigate the semiotic meanings of “#healing” as used in TikTok videos. Using the semiotics in speech acts approach, this study investigates how TikTok videos interact and form meanings between the videos and their followers. The videos chosen are the Top Liked from March to October 2023. For each of the videos with the hashtag #healing, the resulting narration, views, and likes of the post are analysed. Based on these data, the most prominent themes are then identified. Our findings reveal that the hashtag #healing is associated with themes of sadness, laughter, motivation, and gratitude. The results contribute to our understanding of how TikTok users employ speech acts as a form of self-expression and belonging. This study found that the usage of these hashtags on TikTok fosters a connection among its users and unites them to show support for one another. These findings suggest that hashtags work well to aid a type of communication to show support among its users and also form invisible connections online.